KEWIRAUSAHAAN DALAM PERSPEKTIF ONTOLOGY - Rusnandari Retno Cahyani; Mugi Harsono (Universitas Sahid Surakarta, 2019)
This article explores the domain of entrepreneurial research by thematically mapping and assessing the intellectual area of the field. Existing reviews show that the body of knowledge of entrepreneurship is growing, and while important contributions to theoretical and methodological integration are proven, the field is described as phenomenal based, potentially fragmented and suffering from theoretical shortcomings. Based on that entrepreneurship encompasses a variety of entrepreneurial developments throughout the country, we identify 44 relevant journal articles published in the 2009-2018 period. We inventory the development domain of entrepreneurship to provide relevant and comprehensive research organizations. This involves examining the subject of Entrepreneurship research, and inductively synthesizing and categorizing it into the main themes and sub-themes. As such, we offer reliable, ontologically constructed, and practically useful resources. From this basis, we discuss phenomena, problems, inconsistencies, and temporary debates in which new theories of entrepreneurship continue to develop and research can be done. We conclude that Entrepreneurship has several thematic fields that are coherent and rich in potential for future research and theory development.